Influence of TNF-α inhibition on oxidative stress of rheumatoid arthritis patients - F. Cacciapaglia; M.G. Anelli; D. Rizzo; E. Morelli; C. Scioscia; D. Mazzotta; F. Iannone; G. Lapadula (Reumatismo, 2016)
The aim of this study was to assess circulating levels of reactive oxygen metabolites (ROMs) as a marker of oxidative stress in rheumatoid arthritis (RA) patients during an anti-tumor necrosis factor alpha (TNF-α) treatment. We enrolled 40 patients with RA (36 females; age 53±13 yrs) treated with different subcutaneously administered TNF-α inhibitors. The oxidative status was determined on the basis of plasma samples taken before, at 24 and 52 weeks of the anti-TNF-α treatment. Hydroperoxide levels were measured using the d-ROMs test, a useful clinically proven oxidative stress marker. During the anti-TNF-α therapy, we observed a significant reduction in serum ROMs levels in RA patients from 33.2±10 mg H2O2/L at baseline to 29.5±7 and 29.3±9 mg H2O2/L, at 24 and 52 weeks, respectively (p<0.05). We also identified a significant correlation between the oxidative stress status and the disease activity score on 28 joints/C-reactive protein and health assessment questionnaire disability index. The results of our study demonstrate that a good control of the disease with anti-TNF-α agents can reduce oxidative stress in RA patients. However, further studies of larger patient cohorts are needed to confirm these preliminary data.